Bentuk-Bentuk Modernisasi Pertanian Studi Kasus Masyarakat Petani Di Desa Soki Kecamatan Belo Kabupaten Bima Nusa Tenggara Barat - Rostati, Rostati; Haryanto, Lutfin; Atmaja, Jessy Parmawati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Agricultural modernization is a major change in agricultural patterns, namely from a traditional pattern (using various traditional methods) to a more advanced or modern pattern, which includes various aspects including; agricultural institutions and agricultural technology. The purpose of this study was to analyze the forms of agricultural modernization on farmers in Soki Village, Belo District, Bima Regency. The research method used is qualitative. The informants in this study were the farming community and the government in Soki Village. The data techniques in this study were observation, in-depth interviews, and documentation. The data validity used triangulation technique. The results showed forms of agricultural modernization in the farming community in Soki Village, from the paddy field processing stage to the post-harvest stage of rice and shallots, the farming community in Soki Village carried out agricultural activities using technological tools, but not all agricultural activities were carried out and used tools. agricultural technology because the farming community still understands traditional agricultural tools such as the habit of cutting rice, hoes for beating and leveling the land and planting the shallot method still doing the old or traditional